Interdisciplinaridade no processo de diagnóstico e conduta em crianças com distúrbios de linguagem - Baptista, Marta Gonçalves Gimenez (2015)
Child development disorders summon people from different fields of knowledge to reflect on their roles. Within this context, the practice of speech therapy causes continuous reflections based on the singularity of treated cases and their riddles. As a path, the possibility of a dialogue with other areas can respond to important concerns along the career of a professional inSpeech-language Therapy. The experience with children and clinical intervention issues demand from professionals to refer to other disciplines of knowledge as a means to proceed with the interlocution process and understanding of patients as well their clinical condition. The process purpose is to think about the direction of treatment. Objective: This study aims to find evidence of an interdisciplinary practice, focusing on diagnosis and treatment, from case records of children and adolescents with language disorders, shared by phoniatrics and speech-language therapy clinics. Method: This research conducted a descriptive analysis based on Prof. Dr. Mauro Spinelli s clinical collection, whose database included records of children and adolescents attended by him and by the researcher, between the years 1990-2005. The collection is stored in the Interdisciplinary Clinical Unit Professor Dr. Mauro Spinelli, in São Paulo, where the survey took place. Results: In this study, the male gender was prevalent (64.5%) and the language disorder of multifactorial etiology was the most frequent (44%). The treatment commonly adopted was speech-language therapy. Interdisciplinary work was present at the discussion of diagnosis and treatment, at the data presentation, and at the clinical reflections/interlocutions and diagnostic therapy approach. Conclusion: The perspective of professionals involved in the cases reviewed here was guided by the principles of listening and dialogue/interlocution between clinician and patient, and between clinicians, in a process that brought understanding of the child resources and skills, acknowledging that the patient was a subject in a process of constitution. The professionals involved shared the same notion on the subject/child about whom the interlocution was being carried out. These considerations point out the possibility of diagnostic therapy combined with interdisciplinary approach without separating diagnosis and treatment, since this process is continuous